2019
DOI: 10.1002/jso.25722
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mucinous component in hilar cholangiocarcinoma after curative‐intent resection

Abstract: Background The presence of mucinous component has been indicated to have a prognostic value in adenocarcinoma. However, little is known regarding the clinicopathological characteristics and prognosis of hilar cholangiocarcinoma (HC) with mucinous component (HCM). Methods Between January 1996 and December 2014, a total of 61 HCM patients who underwent curative‐intent resection at West China Hospital were retrospectively reviewed. The clinicopathological characteristics and survival of these patients were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(70 reference statements)
2
8
1
Order By: Relevance
“…A panel of clinicopathologic factors have been reported to influence survival of pCCA after curative intent resection [ 12 , 25 , 26 ]. In the current study, high level of preoperative AST (≥85.0 IU/L), high level of preoperative CA19–9 (≥1000 U/mL), vascular resection and poor differentiation of the tumor remained as independent predictors for poor survival, which were in line with previous researches [ 27 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…A panel of clinicopathologic factors have been reported to influence survival of pCCA after curative intent resection [ 12 , 25 , 26 ]. In the current study, high level of preoperative AST (≥85.0 IU/L), high level of preoperative CA19–9 (≥1000 U/mL), vascular resection and poor differentiation of the tumor remained as independent predictors for poor survival, which were in line with previous researches [ 27 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…[11,18,23] A panel of clinicopathologic factors have been reported to in uence survival of pCCA after curative intent resection. [12,25,26] In the current study, high level of preoperative AST (≥85.0IU/L), high level of preoperative CA19-9 (≥1000 U/mL), vascular resection and poor differentiation of the tumor remained as independent predictors for poor survival, which were in line with previous researches [27][28][29][30] The lymph node status have been reported as one of the most important independent prognostic predictor for patients undergoing hepatectomy for pCCA. [17,31] In the present research, N-staging was associated with survival in the univariate analysis, while did not remain as independent predictors of poor survival in multivariate analysis, which maybe attribute to the confounding effect of tumor differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…8 The presence of a mucinous component in hilar CCAs is also associated with worse prognosis, including decreased recurrence-free survival and overall survival. 35 Nevertheless, the 1-year mortality rate of mucinous iCCAs in our four cases and the other 19 cases in the previously published literature is 35%, which is far lower than that of CCAs included in a nationwide study in Thailand (1-year mortality rate = 81.68%). 5 Similarly, a clinicopathological comparison between mucinous and conventional iCCAs in a series from the United States showed that the 1year survival rate of such a rare variant is comparable to that of the conventional counterpart (25% vs. 27%).…”
Section: Discussioncontrasting
confidence: 68%
“…A large series from China reported that there was no significant difference in operation time, intraoperative blood loss, transfusion, and chemotherapy between cases of hilar CCAs with mucinous component (defined by the presence of mucinous component accounting for 5-50% of total tumor volume) and their conventional counterparts. 35 Unlike gastrointestinal mucinous carcinomas, mucinous iCCAs are usually microsatellite-stable. 3 However, data of mismatch-repair and microsatellite status of mucinous iCCAs was limited and controversial.…”
Section: Discussionmentioning
confidence: 99%